2009
DOI: 10.1080/10400430903175622
|View full text |Cite
|
Sign up to set email alerts
|

RESNA Position on the Application of Wheelchair Standing Devices

Abstract: This document, approved by the Rehabilitation Engineering & Assistive Technology Society of North America (RESNA) Board of Directors in March 2007, shares typical clinical applications and provides evidence from the literature supporting the use of wheelchair standers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 28 publications
3
20
0
1
Order By: Relevance
“…However, the non-respond rate of 42% may indicate that the users were dissatisfied with the device or that the device was not used at all. The experiences of increased QoL is consistent with Arva et al [12] who concluded that standing enables participation in activities of daily living and that the upright position could promote the persons self-esteem and social interaction with other people [12,15]. The usability of an assistive device is characterized by the relationship between the user, the assistive device, the activity and the context [16,17].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the non-respond rate of 42% may indicate that the users were dissatisfied with the device or that the device was not used at all. The experiences of increased QoL is consistent with Arva et al [12] who concluded that standing enables participation in activities of daily living and that the upright position could promote the persons self-esteem and social interaction with other people [12,15]. The usability of an assistive device is characterized by the relationship between the user, the assistive device, the activity and the context [16,17].…”
Section: Introductionsupporting
confidence: 77%
“…The use of a standing device can also be part in treatment of bodily structures and prolonged standing may have beneficial effects on various bodily functions and structures [10,11], which in turn may affect the participation in activities in a positive way. The upright body position also allows communication on equal terms for persons with disabilities [9,12]. Standing devices in the present study follow the international classification and terminology ISO 9999 [13] comprising tilt tables, standing frames, standing frames with rear wheels, standing wheelchairs and standing shells.…”
Section: Introductionmentioning
confidence: 99%
“…Successful retraining of the ability to stand enables increased activities of daily living via access to furniture or home appliances, without the need for several home modifications. Additionally, standing is encouraged to initiate walking and to prevent several secondary health problems due to prolonged sitting 2,3 . Current evidence-based strategies 4–6 use standing 7 re-training as an important functional goal during physical and occupational therapy processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Rehabilitation Engineering and Assistive Technology Society of North America (RESNA) argues that the standing posture (achieved in their example by a wheelchair standing device) will give a person with a physical disability considerable bodily benefits in addition to the social and psychological ones that include enhanced psychological wellbeing, independence and productivity (Arva et al 2009). From a medical point of view, it is quite common to recommend standing as a means of managing secondary symptoms in general for people with different physical impairments, among them SMA II.…”
Section: Theoretical Framework the Medical Model Of Disabilitymentioning
confidence: 99%